FAKTOR PENERAPAN PENYUSUNAN LAPORAN KEUANGAN PADA USAHA MIKRO, KECIL DAN MENENGAH (UMKM) - Risal Risal; Renny Wulandari; Reni Dwi Widyastuti (Universitas Putera Batam, 2019)
The main problem in Micro, Small and Medium Enterprises (MSMEs) development is the financial management. Of course it can happen if the agent of MSMEs have the knowledge in the field of accountancy. If the agent of MSMEs desire to earn an extra financial capital, they are required to present the financial report as one of prerequirement of the filings loan to the bank. It means that the agent of MSMEs must be concerned to arrange the financial report as representation of its business condition because of the insistence of the other party. The practice of accountancy in sector of MSMEs Kubu Raya district is still low and have a weakness. The weakness caused a lack of accountancy knowledge as well as the low understanding of the Standard Accounting Finance from the agent of MSMEs. It happened because there is not regulations require that prepare the financial report to the sector of MSMEs. This study aims to analyze the influence of the education level, accountancy understanding, accountancy training, and the business scale to the implementation of preparation its financial report to MSMEs in Kubu Raya district. The population of this study is the agent of MSMEs in Kubu Raya district, West Kalimantan. The technique of sample is using simple random sampling. The data used is the primary data in the form of questionnaire. The techniques of data analysis are using validity test, reliability test, assuming classic test, and double regression test. The result of the research shows that partially the variable of education level, accountancy understanding, and the business scale have influence to the implementation of preparation its financial report. While the variable of accountancy training does not have influence to the implementation of preparation its financial report. Whereas simultaneously the result obtained that four independent variables have influence to its dependent variable.